Determinants and barriers in early tuberculosis treatment in children at a primary health care facility in Kampala, Uganda; A mixed methods study - Wani Muzeyi; Esther Babirekere; Dennis Kalibbala; Achilles Katamba; Joanita Nangendo; Fred C. Semitala; Mary Nyanzi; Victor Musiime (PLoS ONE, 2025)
Background Tuberculosis (TB) remains a leading cause of mortality worldwide, with childhood TB posing unique diagnostic challenges due to its pauci bacillary nature. The World Health Organization emphasizes that these diagnostic difficulties hinder early detection, contributing to delays in treatment initiation, disease progression, and increased morbidity and mortality. Addressing these challenges is critical to achieving the global goal of ending TB as a public health threat by 2030. This study aimed to determine the median time to TB treatment initiation and explore the factors influencing early treatment among children under 15 years at Kisenyi Health Center IV. Methods We conducted a retrospective cohort mixed-methods study. Quantitative data were obtained through a retrospective review of medical records for 152 children under 15 years treated for TB at Kisenyi Health Center IV between February 1, 2021, and February 28, 2023. The median time to treatment initiation was estimated using Kaplan-Meier survival analysis, while Cox proportional hazards regression identified determinants of treatment initiation. Qualitative data were collected through key informant interviews with healthcare workers involved in childhood TB care. Thematic analysis, guided by the Capability, Opportunity, and Motivation Behavior (COM-B) model, was used to identify barriers to early TB treatment. Results A total of 152 children were included in the study. The median time to TB treatment initiation was 39.5 days (IQR: 30,80.9). Pulmonary bacteriologically confirmed TB was the only significant determinant of early treatment initiation (HR: 0.54, 95% CI: 0.31–0.88). Key barriers to timely TB treatment included caregivers’ poor knowledge of childhood TB, referral of children under five to the national referral hospital, inadequate diagnostic equipment and supplies, loss of community follow-up contacts, and high patient volumes. Conclusion Children with TB experience significant treatment delays, underscoring the urgent need for more accessible and rapid diagnostic tools to increase the proportion of bacteriologically confirmed cases and reduce treatment initiation time. Strengthening decentralized TB diagnostic capacity and enhancing caregiver awareness could improve early detection and treatment outcomes.